Menakar Manajemen Resiko Pada Perbankan Syariah - M. Yahya; Saparuddin Siregar; Sugianto (Al - Muamalat: Jurnal Hukum dan Ekonomi Syariah, 2021)
Risk management is an important element whose implementation is very important, especially in the Bank as a financial institution. In a rapidly developing external and internal banking environment, Islamic banks are always faced with various types of risks with varying degrees of complexity and inherent in their business activities. The result of this article is an Islamic bank operational risk management process which includes risk identification, risk assessment, risk anticipation, and risk monitoring arising from bank business activities. In the risk management process, the initial stage of Islamic banks must correctly recognize and understand and identify all risks, existing bank risks (inherent risks) and those that may arise from a new bank business. Furthermore, successively, Islamic banks need to measure, monitor and control risk. This process is continuous, so it becomes a lifecycle. Keywords: Risk management, Islamic Bank